Algorithms, modelling and [dotted V]O^sub 2^ kinetics - Carlo, Capelli; Michela, Cautero; Silvia, Pogliaghi (European journal of applied physiology, 2011)
Issue Title: Pietro di Prampero: A Dedication (pp 321--432) (ProQuest: Abstract omitted; see image)[PUBLICATION ABSTRACT] Erratum DOI: 10.1007/s00421-010-1580-x